Clonal hematopoiesis of indeterminate potential (CHIP), vascular somatic mutation, and cardiovascular disease: A narrative review - Nicole Powell; Richard M Cubbon; Marc A Bailey; Kathryn J Griffin; Lee Roberts; Chew Cheng (Vascular Medicine, 2026)
Somatic cell DNA mutations accumulate with age, and can give cells a survival advantage, resulting in their clonal expansion over time. We know that these mutations can lead to cancer, but the growing application of next-generation sequencing across multiple ‘healthy’ tissues has revealed their ubiquity and relevance to noncancer pathology. Indeed, these mutations may play a role in cardiovascular disease (CVD), particularly in the progression of atherosclerosis and other vascular diseases. This review examines the impact of somatic mutations in both blood and cardiovascular tissues, focusing particularly on clonal hematopoiesis of indeterminate potential (CHIP), and its association with systemic inflammation. CHIP mutations, present in hematopoietic stem cells and their progeny, have been associated with increased risk of CVD, possibly by promoting pro-inflammatory pathways that drive atherosclerosis, although some data suggest CHIP may also arise due to an inflammatory milieu. These somatic variants, and non-CHIP variants, have been detected in atherosclerotic plaques, raising questions about their direct role in atherogenesis and vascular remodeling. Understanding the current research on somatic mutations in blood and cardiovascular tissues may uncover new insights into CVD progression and highlight potential therapeutic targets.